Study of Environmental Education Programs and Behavior Change in Ethiopia - Tadesse, Almaz (International Journal of Environmental Sciences, 2024)
Purpose: The aim of the study was to investigate the Study of Environmental Education Programs and Behavior Change in Ethiopia. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Environmental education programs in Ethiopia have successfully increased awareness and promoted sustainable practices among communities. These initiatives have focused on issues like deforestation, soil erosion, and water conservation, encouraging behaviors such as waste reduction and sustainable agriculture. Community involvement and stakeholder engagement have been crucial in maintaining these positive changes. Scaling up these efforts is essential for long-term environmental sustainability in Ethiopia. Unique Contribution to Theory, Practice and Policy: Theory of planned behavior (TPB), social learning theory & diffusion of innovations theory may be used to anchor future studies on the impact of urban green spaces on air quality in Bangkok. Advocate for the integration of environmental education into formal educational curricula at all levels, emphasizing hands-on learning and practical applications. Advocate for policies that mandate or incentivize environmental education across educational systems and workplaces.